2012
DOI: 10.1007/s00125-012-2662-6
|View full text |Cite
|
Sign up to set email alerts
|

Elevated NEFA levels impair glucose effectiveness by increasing net hepatic glycogenolysis

Abstract: Aims/hypothesis Acute hyperglycaemia rapidly suppresses endogenous glucose production (EGP) in non-diabetic individuals, mainly by inhibiting glycogenolysis. Loss of this 'glucose effectiveness' contributes to fasting hyperglycaemia in type 2 diabetes. Elevated NEFA levels characteristic of type 2 diabetes impair glucose effectiveness, although the mechanism is not fully understood. Therefore we examined the impact of increasing NEFA levels on the ability of hyperglycaemia to regulate pathways of EGP. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 49 publications
(74 reference statements)
1
13
0
Order By: Relevance
“…Second, there may be differences in physiology between fasting and postprandial NEFA kinetics that we are not able to investigate but that may explain our null findings for fasting NEFA and insulin sensitivity. For instance, some experimental studies using clamp protocols found that fasting NEFA was a weak predictor of insulin sensitivity compared with postprandial concentrations of NEFA [11,50]. Inefficiencies in NEFA uptake into the adipose tissue (as seen in individuals with obesity and larger WC) following postprandial TAG lipolysis via lipoprotein lipase may result in NEFA spilling over into the blood and a subsequent increase in circulating NEFA [51], which may be more metabolically active given postprandial activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, there may be differences in physiology between fasting and postprandial NEFA kinetics that we are not able to investigate but that may explain our null findings for fasting NEFA and insulin sensitivity. For instance, some experimental studies using clamp protocols found that fasting NEFA was a weak predictor of insulin sensitivity compared with postprandial concentrations of NEFA [11,50]. Inefficiencies in NEFA uptake into the adipose tissue (as seen in individuals with obesity and larger WC) following postprandial TAG lipolysis via lipoprotein lipase may result in NEFA spilling over into the blood and a subsequent increase in circulating NEFA [51], which may be more metabolically active given postprandial activity.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a sizeable literature investigating the role of total NEFA concentration in diabetes, there are important gaps in this research. The majority of previous studies have used animal models or cell lines [6,7], have been short term human trials [8][9][10][11] or have been epidemiological studies that only looked at total NEFA and not individual fatty acids [12][13][14]. To date, there have been no longitudinal studies examining the role of the serum NEFA composition on the pathogenesis of diabetes, which is critical given the protracted natural history of diabetes and the growing appreciation of the divergent effects of individual fatty acids.…”
Section: Introductionmentioning
confidence: 99%
“…This may be attributed to the brisk release of insulin from the pancreas activating the LpL which reduces TG through hydrolysis. Furthermore, the results suggest that DT may have reversed increased free fatty acids which affect adequate glucose metabolism in diabetic patients [ 81 , 82 ]. Presence of insulin stimulates fatty acids biosynthesis, incorporates fatty acids into TG in the liver and adipose tissue [ 83 ] by inhibiting hormone sensitive lipase (HSL), increases utilization of glucose, and decreases mobilization of free fatty acids from the fat depositions [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of plasma insulin, C-peptide, glucagon, and cortisol concentrations were measured by radioimmunoassay in the Diabetes Research Center Hormone Assay Core, as previously reported ( 19 ). D2G concentrations were measured by gas chromatography–mass spectrometry, as previously described ( 20 ). Plasma epinephrine and norepinephrine levels were determined using high-performance liquid chromatography (HPLC; Quest Diagnostics, Chantilly, VA).…”
Section: Methodsmentioning
confidence: 99%